Tofu Factory Liquid Waste for Making Struvite with Canted Vertical Reactors - Sutiyono; Luluk edahwati; Kartika Pratiwi; Achmad Fanani (International Journal of Eco-Innovation in Science and Engineering, 2020)
Struvite is a white crystal, chemically known as magnesium ammonium phosphate hexahydrate (MgNH4PO4.6H2O). Tofu factory liquid waste is waste that can be reused because of its content. Tofu factory liquid waste can potentially pollute the environment. This research aimsto analyze the manufacture of struvite by utilizing the phosphate content contained in the liquid waste of tofu factories using vertical canted column reactors which can reduce environmental pollution due to liquid waste of tofu factories. This study uses a vertical canted column reactors by mixing anequimolar 1: 1: 1 MgCl2: NH4OH: H3PO4 solution. Struvite crystallization process operates at a temperature variation of 30°C,35°C,40°C,45.50°Cand a pH of 8, 9,10,11,12 by maintaining the air rate of 0.5 liters minute-1 and a MAP (Magnesium Ammonium Phosphate)flow of 56 ml minutes-1 as a whole. The crystallization process runs until a steady state conditionis reached. Then, the struvite crystals obtained were filtered and dried at room temperature for 24 hours. After that struvite crystals were analyzed using XRF, XRD, and SEM. The results of the study obtained the best phosphate conversion of 24.935% at 30°C and pH 8.